Case Report: Hypodipsic hypernatremia secondary to hydrocephalus in a dog - Maddisen W. Antes; Amelia C. Corona; Helena Rylander (Frontiers in Veterinary Science)
A 6-year-old male castrated golden retriever was presented for inappetence, lethargy, and progressive obtundation. A chemistry panel showed hypernatremia (>190 mmol/L) and hyperchloremia (157 mmol/L). Brain magnetic resonance imaging (MRI) showed severe congenital hydrocephalus with compression of major brain structures, including marked thinning of gray and white matter of the prosencephalon. Results of cerebrospinal fluid (CSF) analysis were within the reference range. A hypodipsic hypernatremia was suspected secondary to dysregulation of the osmoreceptors controlling the thirst center due to progression of hydrocephalus. The dog was treated with intravenous (IV) fluids to slowly reduce the hypernatremia over several days. Mental status improved with normalization of the blood sodium level. Increased stress due to a long car ride and a change in routine may have been the catalyst for the hypodipsia. Hypodipsic hypernatremia is a rare complication of hydrocephalus and should be on the differential list when a sudden change in mentation occurs in dogs with hydrocephalus.